2015
DOI: 10.1038/cddis.2015.148
|View full text |Cite
|
Sign up to set email alerts
|

1α, 25-Dihydroxyvitamin D3 and the vitamin D receptor regulates ΔNp63α levels and keratinocyte proliferation

Abstract: 1α, 25-dihydroxyvitamin D3 (VD3), a secosteriod that has been explored as an anti-cancer agent, was also shown to promote cell survival. Its receptor, the Vitamin D Receptor (VDR), is a direct target of the proto-oncogene ΔNp63α, which is overexpressed in non-melanoma skin cancers. The interconnection between VDR/VD3 signaling and ΔNp63α, led us to examine whether VDR/VD3 signaling promotes keratinocyte proliferation by regulating ΔNp63α levels. Our data demonstrate that VDR regulates ΔNp63α expression at both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 51 publications
8
27
0
Order By: Relevance
“…Skin tissue microarrays used in this study included normal skin (N=53), a precursor to squamous cell carcinoma/actinic keratosis (AK) (N=66), cutaneous squamous cell carcinoma (SCC) (N=59) and cutaneous basal cell carcinoma (BCC) (N=57) sections (Additional le 7: Table S1). Consistent with a previous report from our lab [6], ΔNp63α is signi cantly upregulated in AK, SCC and BCC skin tissues compared with normal skin ( Figure 1A and B and Additional le 8: Table S2). ERK3 protein was also shown to be expressed in all four types of skin sections and mainly localized to the cytoplasm of the cells ( Figure 1A and C and Additional le 8: Table S2).…”
Section: Erk3 Expression Is Upregulated In Nmsc and Positively Correlsupporting
confidence: 92%
See 2 more Smart Citations
“…Skin tissue microarrays used in this study included normal skin (N=53), a precursor to squamous cell carcinoma/actinic keratosis (AK) (N=66), cutaneous squamous cell carcinoma (SCC) (N=59) and cutaneous basal cell carcinoma (BCC) (N=57) sections (Additional le 7: Table S1). Consistent with a previous report from our lab [6], ΔNp63α is signi cantly upregulated in AK, SCC and BCC skin tissues compared with normal skin ( Figure 1A and B and Additional le 8: Table S2). ERK3 protein was also shown to be expressed in all four types of skin sections and mainly localized to the cytoplasm of the cells ( Figure 1A and C and Additional le 8: Table S2).…”
Section: Erk3 Expression Is Upregulated In Nmsc and Positively Correlsupporting
confidence: 92%
“…Formalin-xed, para n-embedded human skin tissue microarrays described previously [6] were used for co-immunostaining studies. Human tissue samples consisted of normal skin (N=53), actinic keratosis (AK) (N=66), cutaneous squamous cell carcinoma (SCC) (N=59), and basal cell carcinoma of the skin (BCC) (N=57).…”
Section: Tissue Immuno Uorescence Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the kidney, 25(OH)VitD is further hydroxylated to 1,25-dihydroxyvitamin D [1,25(OH) 2 VitD]. 1,25(OH) 2 VitD is the major biologically active metabolite and plays an important role in decreasing the risk of many diseases, including common cancers, cardiovascular disease, autoimmune disease, and chronic kidney disease (13)(14)(15)(16)(17). Most recently, we have demonstrated that 1,25(OH) 2 VitD also appears to be important for the health of the eye (18).…”
mentioning
confidence: 99%
“…Also, 1,25(OH)2D3 blocks mitogenic signaling, including that of estrogen, epidermal growth factor (EGF), and insulin-like growth factor 1, and upregulates growth inhibitors such as transforming growth factor β (TGF-β) [178]. In addition, 1,25(OH)2D3 activates VDR-mediated apoptosis [179].…”
Section: Vitamin D and Uterine Leiomyomamentioning
confidence: 99%